Children with neurodisability and feeding difficulties: a UK survey of parent-delivered interventions. Issue 1 (23rd June 2021) - Taylor, Helen; Pennington, Lindsay; Craig, Dawn; Morris, Christopher; McConachie, Helen; Cadwgan, Jill; Sellers, Diane; Andrew, Morag; Smith, Johanna; Garland, Deborah; McColl, Elaine; Buswell, Charlotte; et al.
Abstract : Background: Eating, drinking and swallowing difficulties (EDSD) are common in children with neurodisability, and have physical and non-physical causes. EDSD have substantial impacts on the child and family. Little is currently documented about what advice is usually given by professionals, including the interventions commonly used, and what informally constitutes 'best clinical practice'. We aimed to identify current UK practice of parent-delivered interventions for EDSD for children with neurodisability, and the outcomes valued by professionals and parents. Methods: Two populations were sampled: health professionals working with children and young people (aged 0–18 years) with neurodisability who experience EDSD (n=421); parents of children with neurodisability aged up to 12 years who experience EDSD (n=359). Questionnaires were developed based on the findings from updates of three systematic reviews, a mapping review of interventions used with this population, and in consultation with health professionals and parents. The questionnaires were distributed through UK health professional and parent networks and mainstream and specialist schools. Results: Diverse professional groups, including speech and language therapists, occupational therapists, paediatricians and dietitians, support children with EDSD and neurodisability. A range of parent-delivered interventions, such as food and drink modification, positioning and modification of mealtime environment, were recommended by health professionals and are used by and acceptable to parents. Health professionals thought the interventions were effective but parents' views were less consistent. Both health professionals and parents rated better general health and improved nutrition as the most important outcomes. Conclusions: These survey findings outline current UK practice of parent-delivered interventions for EDSD in young children with neurodisability. The survey suggests key outcomes to measure in assessing the effectiveness of interventions. Further research is now needed to fully evaluate the effectiveness of interventions and move towards an evidence-based approach to best practice.